Synthesis of [Cp'Fe(η3-BH4)] and its conversion to [Cp'FeBH2]3 - Maekawa, Miyuki; Daniliuc, Constantin G.; Jones, Peter G.; Hohenberger, Johannes; Sutter, Jörg; Meyer, Karsten; Walter, Marc D. (European Journal of Inorganic Chemistry, 2013)
Salt metathesis of [Cp'FeI] [1, Cp' = η-1,2,4- (MeC)CH] and NaBH (2 equiv.) in tetrahydrofuran yields the low-spin iron complex [Cp'Fe(ηBH)] (2), which is thermally unstable and degrades slowly to the trimeric complex [Cp'FeBH] (3) and H. Both molecules have been fully characterized by various spectroscopic techniques. An X-ray structure analysis of 3 confirms its nature and reveals rather long B-B distances of 1.883(9) Å. DFT methods in combination with three complementary approaches [Wiberg bond indices (WBI), atoms in molecules (AIM) and compliance constants] have been used to explain the bonding in these iron(II) complexes. All methods predict a weak bonding interaction between the boron atoms in 3. © 2013 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: Iron; Hydride ligands; Sandwich complexes; Density functional calculations; Boranes; Borohydrides